2004
DOI: 10.1081/dis-120037687
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Behavior of Naphthenic Acids and Multivalent Cations in Systems with Oil and Water. I. A Pendant Drop Study of Interactions Betweenn‐Dodecyl Benzoic Acid and Divalent Cations

Abstract: Dynamic interfacial tension (IFT) measurements were used to investigate the interactions between a dissociated model naphthenic acid (p-(n-dodecyl) benzoic acid) and various divalent metallic cations (Mg 2þ , Ca 2þ , Sr 2þ , and Ba 2þ ) across a toluene/hexadecane -water interface. The measurements were performed by using the pendant drop technique. The results obtained, plotted as IFT vs. time gave curves with similar shapes but different slopes and levels of the equilibrium IFT, depending upon the acid and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 21 publications
(9 reference statements)
3
53
0
Order By: Relevance
“…The rest of the studied brine solutions (higher CaCl 2 salinities and Na 2 SO 4 ) not only did not alter the wettability of the sample to water-wet but some of them turned the limestone sample to more oil wet. Several studies conducted on the forces between carboxylic acid coated surfaces in divalent electrolyte solutions (Brandal et al, 2004;Brandal and Sjoblom, 2005a;Brandal et al, 2005b;Ederth and Claesson, 2000) proved that multivalent cations in solution, especially Ca +2 , have high affinity towards the carboxylic groups. All of the measurements were conducted at the ambient temperature and therefore, the effect of higher temperatures on wettability was not considered in this study.…”
Section: Results For Indiana Limestone Samplesmentioning
confidence: 99%
“…The rest of the studied brine solutions (higher CaCl 2 salinities and Na 2 SO 4 ) not only did not alter the wettability of the sample to water-wet but some of them turned the limestone sample to more oil wet. Several studies conducted on the forces between carboxylic acid coated surfaces in divalent electrolyte solutions (Brandal et al, 2004;Brandal and Sjoblom, 2005a;Brandal et al, 2005b;Ederth and Claesson, 2000) proved that multivalent cations in solution, especially Ca +2 , have high affinity towards the carboxylic groups. All of the measurements were conducted at the ambient temperature and therefore, the effect of higher temperatures on wettability was not considered in this study.…”
Section: Results For Indiana Limestone Samplesmentioning
confidence: 99%
“…[27] Thus, from the observations and explanations above, the effects of pH, counterions, and acid structure on the film stability may be summarized in the following way: . As described in the theory part, the binding strength between the compounds is also fixed by the degree of hydration of the cations; the more water of hydration that surrounds the cation the less preferable it is to be located at a water-oil interface.…”
Section: Resultsmentioning
confidence: 99%
“…IFT studies using a model naphthenic acid showed that the process of metal naphthenate formation is initiated by diffusion of the amphiphilic acid to the oil-water interface where it dissociates to the more interface-active anion (Brandal et al 2004). If the water phase contains cationic species, the extent to which IFT changes will depend on the nature and concentration of the cation in the water and naphthenic acid in oil.…”
Section: Identification Quantification and Characterization Of Naphtmentioning
confidence: 99%